Defect-passivation of organometal trihalide perovskite with functionalized organic small molecule for enhanced device performance and stability. (May 2021) - Choi, Joonhyuk; Kamaraj, Eswaran; Park, Hansol; Jeong, Bum Ho; Baac, Hyoung Won; Park, Sanghyuk; Park, Hui Joon
Abstract: Defects in solution-processed organic and inorganic halide perovskite thin films deteriorate their photovoltaic performance and stability. Here, a bisimidazole-based organic small molecular hole transport material (HTM) that can suppress interfacial defects of the perovskite with its functional groups working as Lewis bases is newly introduced. Surface passivation of perovskite film leads to the reduction in non-radiative recombination trap density as well as the improvement of its crystallinity, consequently enhancing the efficiency of perovskite solar cell (PSC) from 16.3% to 18.3% with superior stability, preserving 92% of its initial efficiency for 500 h in an atmosphere. Highlights: A bisimidazole-based organic hole transport material (HTM) is synthesized. Lewis-base functional groups of HTM are proved to passivate defects of perovskite such as under-coordinated Pb 2+ ions. The designed organic HTM is introduced between NiOx HTM and photoactive layer for improving their interfacial properties. This modification improves crystallinity of perovskite and reduces non-radiative recombination in solar cell devices. The efficiency increases from 16.3% to 18.3% with organic HTM. Defect-passivated device has superior stability, preserving 92% of its initial efficiency for 500 h in air.